2022
DOI: 10.1002/ijc.33934
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk and mortality after solid organ transplantation: A population‐based 30‐year cohort study in Finland

Abstract: Cancer is a significant cause of morbidity and mortality after solid organ transplantation (SOT) and related to lifelong immunosuppression. This retrospective registry study assessed for the first time in Finland population-based cancer risk and cancer mortality after all SOTs (lung and childhood transplantations included) as standardized incidence ratios (SIRs) and standardized mortality ratios (SMRs). Data from transplant registries were linked with the data of Finnish Cancer Registry and Statistics Finland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 55 publications
5
31
0
2
Order By: Relevance
“…For example, skin cancer was the most common malignancy diagnosed after SOT in our cohort, followed by lymphoma and kidney cancer. 35 In concordance with the largest study of cancer risk in SOT recipients, our data demonstrated that the majority of liver cancer diagnoses occur within the first year of transplantation and kidney cancer incidence was highest in kidney transplant recipients. 5 A recent population-based cohort study in Finland found increased incidence of cancer rates in heart and lung transplant recipients in comparison to kidney and liver transplant recipients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, skin cancer was the most common malignancy diagnosed after SOT in our cohort, followed by lymphoma and kidney cancer. 35 In concordance with the largest study of cancer risk in SOT recipients, our data demonstrated that the majority of liver cancer diagnoses occur within the first year of transplantation and kidney cancer incidence was highest in kidney transplant recipients. 5 A recent population-based cohort study in Finland found increased incidence of cancer rates in heart and lung transplant recipients in comparison to kidney and liver transplant recipients.…”
Section: Discussionsupporting
confidence: 89%
“…5 A recent population-based cohort study in Finland found increased incidence of cancer rates in heart and lung transplant recipients in comparison to kidney and liver transplant recipients. 35 However, upon adjusting for immunosuppressive medications, we found no difference in the rates of malignancy between SOT groups, indicating the increased risk may be due to the medication. In liver transplant recipients, cumulative exposure to tacrolimus increased the risk of cancer.…”
Section: Discussionmentioning
confidence: 64%
“…Young patients who undergo solid‐organ transplantation (SOT) have decreased life expectancy when compared to the general population due to post‐transplantation complications such as acute or chronic graft rejection, infection, and death from malignancy. 6 , 7 There is a nearly 9% risk of developing a noncutaneous nonlymphomatous malignancy at 5 years, and for all malignancies, there is a 30% incidence rate at 10 years of post‐SOT. 8 , 9 Therefore, early detection and screening in post‐transplant patients is imperative to improve long‐term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppression is a risk factor for melanoma, BCC and SCC. Populations with compromised immunity at increased risk include organ transplant recipients [ 118 ], those diagnosed with HIV/AIDS (fourfold increased risk of melanoma) [ 119 , 120 ], and those treated for rheumatoid arthritis (~ 1.3-fold increased risk of KC and melanoma) [ 121 ], inflammatory bowel disease (~ 1.5-fold increased risk of KC), and some lymphoproliferative disorders including non-Hodgkin lymphoma and chronic lymphocytic leukaemia (~ twofold increased risk of melanoma) [ 122 ]. In solid-organ transplant recipients the magnitude of the increased risk differs between skin cancer types: the increased risk in a high ambient UV radiation environment is two–threefold for melanoma, six–tenfold for BCC, and as high as 100-fold for SCC [ 123 ].…”
Section: Harms Of Exposure To Uv Radiationmentioning
confidence: 99%